Cover, Content, and Editorial Note from Borneo J Med Lab Tech Vol. 2 No. 2 April 2020 - Chief Editor of Borneo J Med Lab Tech (Borneo Journal of Medical Laboratory Technology, 2020)
Assalamu’alaikum Wr. Wb.Alhamdulillahirabbil ‘alamin. After a long wait for almost 12 years from the first stand, finally the scientific journal of the Department of Analyst Health (Medical Laboratory Technology) Universitas Muhammadiyah Palangkaraya can be published. BJMLT published every 6 months (2 issues/year) every October and April. The aim of this journal is to publish high-quality articles dedicated to all aspects of the latest outstanding developments in the field but not limited to Blood transfusion, Clinical Chemistry, Hematology, Histopathology, Immunology, Microbiology, Parasitology, Toxicology, Food and Beverage Analysis, Molecular Biology, Medical Biology, and related fields that are of interest to medical laboratory technologies, such as epidemiology, health promotion, professional ethics, and laboratory management, It was first published online in October 2018 usingOpen Journal System (OJS) 3.1 platform with e-ISSN 2622-6111 by url http://journal.umpalangkaraya.ac.id/index.php/bjmlt.This edition contains 6 articles consisting of Hematology, Microbiology, Clinical Chemistry and epidemiology topics. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions.The publication of BJMLTcertainly participate in disseminating the results of research and review of science and technology development conducted by lecturers and researchers from UM Palangkaraya and other universities.The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition on october 2020.Wassalamu’alaikum Wr. Wb.Palangka Raya, April 2020Editor-in-Chief